The ability to solve problems and its relationship to the level of ambition for second year secondary school students. A field study at two secondary schools at the town of Magra, a district of the Wilaya of M’sila. Algeria - bennaceur, ferhat; benkrima, bouhafs (Journal of Social Sciences and Humanities, 2025)
The study aimed to identify the nature of the relationship between the ability to solve problems and the level of ambition among a sample of second-year secondary school students who are conducting their studies during the 2019/2020 academic year, in the town of Magra a district of the Wilaya of M’sila. The sample included (109) students drawn in a stratified random manner according to two variables gender and specialty. To achieve the objectives of the study, the two researchers used two tools to collect data, one for measuring the ability to solve problems, and the other for measuring the level of ambition. After analyzing the data, the study found that there was no statistically significant correlation between the ability to solve problems and the level of ambition. Moreover, the results of the study showed that there are statistically significant differences in the ability to solve problems linked to the gender variable in favor of male students. And the existence of statistically significant differences in the level of ambition linked to the variable of gender in favor of female students. While the study did not show the presence of statistically significant differences in the ability to solve problems and in the level of ambition attributed to the specialty variable.